Description of the children with aortic stenosis at the Chris Hani Baragwanath Academic Hospital over 20 years - Mendes, Jacqueline Faria (My University, 2017)
Introduction Data about congenital heart disease, in particular aortic stenosis, remains scarce from the African continent. Aortic stenosis can be supravalvular, valvular or subvalvular. Anecdotal evidence in our setting suggested that the aortic stenosis subtype profile differed to that of western literature. A retrospective record review of all children presenting to Chris Hani Baragwanath Academic Hospital with aortic stenosis from 1984 to June 2015 was undertaken. Results The majority of the patients 76% (n=205), presented with subvalvular aortic stenosis. Boy and girl children were almost equally effected. The echocardiographical peak instantaneous gradient measured across the stenotic left ventricular outlet obstruction varied depending on the level of stenosis. The majority of subvalvular aortic stenoses 123 (62%) presented with mild peak instantaneous gradients (p<0.005) at presentation, most likely due to its copresence with ventricular septal defects. Furthermore, the majority of children with subvalvular aortic stenosis presented with co-existing cardiac lesions. Consequently, the majority of patients with discrete subaortic stenosis (n=116, 61%) required surgical intervention. Conclusion DSAS was highlighted as the predominant aortic stenosis subtype in this population. This is different to western literature where valvular aortic stenosis is most common. Boys were not found to be significantly more affected than girls, as reported in other countries. The majority of patients had associated cardiac lesions, and most of which required invasive surgical treatment. Key words Congenital cardiac lesions, aortic stenosis, valvular, subvalvular, peak instantaneous gradient, isolated discrete subvalvular stenosis.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand Johannesburg, in fulfilment of the requirements for the degree of Master of Medicine (Med) in the branch of Paediatrics. Johannesburg, 12 October 2017.
Keywords: Aortic Stenosis, Subvalvular; Heart Diseases